Зонування водопровідних мереж - Спичак, П. О. (ХНУРЕ, 2023)
This work is devoted to the optimization of the structure of the water supply network by means of zoning. The task of optimal zoning of water supply networks consists of two sub-tasks: selection of isolated zones of nodes with excess pressure exceeding the specified value in the water supply network; calculation of the parameters of the pressure regulators installed at the entrances to the selected zones. A method based on the width search method is proposed for zone selection. To calculate the parameters of pressure regulators using the Newton and Nelder-Mead method, the deterministic equivalent of the stochastic model of the quasi-stationary modes of operation of the water supply network was solved.
Keywords: водопроводна мережа; зонування мережі; стохастична модель квазістаціонарних режимів системі подачі та розподілу води